Determinants of retirement saving behavior among employees in Kota Cemerlang, Ayer Keroh, Melaka / Aimi Hanis Abd Halim and Mohamad Izzudin Ismail - Abd Halim, Aimi Hanis; Ismail, Mohamad Izzudin (Faculty of Business and Management, 2014)
This research conducted focusing on the factors that influence retirement savings behavior among employess in Kota Cemerlang, Ayer Keroh, Melaka. Retirement saving behavior is very important to ensure that all working Malaysian citizens have knowledge about retirement scheme. In Malaysia, there still many people not aware towards saving for their retirement. In support of the government endeavor, many initiatives had been developed to help the public to create savings for their retirement. For example, the 1Malaysia Retirement Savings Scheme had been launched by our Prime Minister, Datuk Seri Najib Tun Razak in Budget 2010, introduced as government initiative to ensure that the self-employed and have no regular income during their retirement savings. This scheme was effective from January 3, 2010.